Exploring educational dynamics: Insights from the rhetoric and realities of leaders, teachers, students, and parents' contributions to improving educational quality - Getu Shiferaw Wolle (College of education, Bahir Dar University, 2024)
This issue presents the multifaceted dynamics shaping education and institutional development. Drawing on a diverse collection of ten research findings and one book chapter review, it explores factors influencing educational outcomes, such as social media use, parental involvement, teacher effectiveness, culturally responsive pedagogy, inclusive education challenges, strategic management, emotional intelligence, and the role of leadership in research productivity. Additionally, the current issue brings to light some factors that influence education quality, taken from studies that examine the contributions and impacts of key stakeholders, including educational leaders, teachers, students, and parents. This editorial provides insights that underscore the significance of addressing these interconnected issues to improve educational quality and promote institutional success in Ethiopia and beyond.